Relationships among identity statuses and social adaptation at school indices - Legkauskas, Visvaldas (Psichologija, 2000)
Research report on relationship between ego identity and aspects of social functioning at school is presented. Subjects were 110 Lithuanian 12-th graders, 46 male and 64 female. For the assessment of identity status the Extended Objective Measure of Ego Identity Status, final revision (EOMEIS-2) developed by Adams, Bennion, and Huh (1989) was translated into Lithuanian language. Self-report Subjective Social Well-Being Scale and Problem Behavior Scale completed by teachers, as well as popularity in class, served as functioning in school indices and also as a criteria for predictive validation of the EOMEIS-2.EOMEIS showed satisfactory reliability and construct and criterion validity. Ideological moratoriums were more popular than ideological achievers. Interpersonally committed statuses had better subjective social adaptation than interpersonally non-committed statuses. Interpersonal diffusions and foreclosures displayed less problem behaviors than interpersonal moratoriums and achievers.
Keywords: identity status; social adaptation; school; indices